# Homework Help: Wave mechanics : self-adjoint problem

1. Sep 12, 2009

### noblegas

1. The problem statement, all variables and given/known data
The operators P and Q are self-adjoint and satisfy the commutation relation [P,Q]=ic where c is a real number. Show that the operator [P,Q] is anti-self-adjoint, that is , that the adjoint of the operator is the negative of the operator, consistent with the right-hand side of the equation.

2. Relevant equations

3. The attempt at a solution

I know a self-adjoint operator Q*=Q where * represents the dagger. [P,Q]=(PQ-QP)*phi=ic=0=PQphi-QPphi= PQ*phi-Q*Pphi=0?

2. Sep 12, 2009

### gabbagabbahey

Why are you setting $[P,Q]$ equal to zero? and what is 'phi'...an example wavefunction?....There is no need to introduce any wavefunctions here.

By definition, $[P,Q]=PQ-QP$...you are told that this is equal to $ic$.

What is the definition of $[P,Q]^\dagger$?

3. Sep 13, 2009

### noblegas

Right... matrices don't commute. By definition , $[P,Q]^\dagger$=$[Q,P]=QP-PQ$

I think I got it . PQ=ic+QP => [Q,P]=QP-PQ=QP-(ic+QP)=-ic ?

Last edited: Sep 13, 2009
4. Sep 13, 2009

### gabbagabbahey

While its true that $[P,Q]^{\dagger}=[Q,P]$ (but only since $Q$ and $P$ are Hermitian), that's not really the definition of $[P,Q]^{\dagger}$. In fact, it's basically the very thing you are trying to prove, so I wouldn't use it as the basis of your proof!

By definition,

$$[P,Q]^{\dagger}=(PQ-QP)^{\dagger}=(PQ)^{\dagger}-(QP)^{\dagger}$$

Now, use the fact that $(AB)^{\dagger}=B^{\dagger}A^{\dagger}$ for any two operators $A$ and $B$, along with the fact that $Q$ and $P$ are Hermitian...

5. Sep 13, 2009

### noblegas

$$[P,Q]^{\dagger}=(PQ-QP)^{\dagger}=(PQ)^{\dagger}-(QP)^{\dagger}$$=$$Q^{\dagger}P^{\dagger}-P^{\dagger}Q^{\dagger}$$; since $$Q^{\dagger}=Q$$ , then $$P^{\dagger}=P$$, therefore $$Q^{\dagger}P^{\dagger}-P^{\dagger}Q^{\dagger}=QP-PQ=[Q,P]$$

therefore $$[P,Q]^{\dagger}=[Q,P]$$

6. Sep 13, 2009

### gabbagabbahey

Right, but your problem statement doesn't actually tell you the operators are Hermitian, so you won't want to use that.

Instead, just take the adjoint of both sides of the equation you are given...

$$[P,Q]=ic\implies [P,Q]^{\dagger}=(ic)^{\dagger}=-ic=-[P,Q]$$